2014
DOI: 10.1186/1748-717x-9-118
|View full text |Cite
|
Sign up to set email alerts
|

Early results of urethral dose reduction and small safety margin in intensity-modulated radiation therapy (IMRT) for localized prostate cancer using a real-time tumor-tracking radiotherapy (RTRT) system

Abstract: BackgroundWe prospectively assessed the utility of intensity-modulated radiation therapy (IMRT) with urethral dose reduction and a small margin between the clinical target volume (CTV) and the planning target volume (PTV) for patients with localized prostate cancer.MethodsThe study population was 110 patients in low- (14.5%), intermediate- (41.8%), and high-risk (43.6%) categories. Three gold fiducial markers were inserted into the prostate. A soft guide-wire was used to identify the urethra when computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 19 publications
(29 reference statements)
0
30
0
Order By: Relevance
“…They noted similar rectal toxicity in-between two cohorts. Shimizu et al 65 reported on 110 patients treated with real-time tracking of fiducial markers and a PTV margin of 3 mm. They noted low adverse events with favourable relapse-free survival suggesting that the small margins did not compromise prostate coverage with their localization protocol.…”
Section: Use Of Daily Ultrasoundmentioning
confidence: 99%
“…They noted similar rectal toxicity in-between two cohorts. Shimizu et al 65 reported on 110 patients treated with real-time tracking of fiducial markers and a PTV margin of 3 mm. They noted low adverse events with favourable relapse-free survival suggesting that the small margins did not compromise prostate coverage with their localization protocol.…”
Section: Use Of Daily Ultrasoundmentioning
confidence: 99%
“…≈1.5Gy) compared with the nearby organs at risk (OAR); rectum, urethra and bladder, with α/β values of 3–5 Gy [ 2 , 3 ]. A treatment strategy, such as intentionally under-dosing areas of potentially lower tumor burden, for example the periurethral transitional zone of the prostate, may be used to reduce the risk of radiation induced urinary toxicity [ 4 6 ]. However, the risk of rectal toxicity is a major concern when designing prostate dose-escalation studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of urethral sparing with both EBRT and brachytherapy have demonstrated unacceptable levels of local recurrence ( 26 ). Urethral dose reduction (UDR) aims to reduce the risk of late urinary toxicity without significantly increasing the risk of local recurrence ( 27 ). Urethral catheter (UC) placement prior to simulation is a commonly used technique to identify the prostatic urethra.…”
Section: Introductionmentioning
confidence: 99%